2021
DOI: 10.47102/annals-acadmedsg.202178
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of non-cystic-fibrosis bronchiectasis in multiethnic Singapore: A prospective cohort study at a tertiary pulmonology centre

Abstract: Introduction: Non-cystic fibrosis bronchiectasis (NCFB) is a highly heterogenous disease. We describe the clinical characteristics of NCFB patients and evaluate the performance of Bronchiectasis Severity Index (BSI) in predicting mortality. Methods: Patients attending the bronchiectasis clinic between August 2015 and April 2020 with radiologically proven bronchiectasis on computed tomography were recruited. Clinical characteristics, spirometry, radiology, microbiology and clinical course over a median period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A previous cohort study conducted in Taiwan also indicated the prevalence of bronchiectasis to be dominant in women [13]. Additionally, a Singaporean cohort study identified the preponderance of women [14]. However, contradicting results have also been identified in some studies, suggesting further investigation.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A previous cohort study conducted in Taiwan also indicated the prevalence of bronchiectasis to be dominant in women [13]. Additionally, a Singaporean cohort study identified the preponderance of women [14]. However, contradicting results have also been identified in some studies, suggesting further investigation.…”
Section: Introductionmentioning
confidence: 91%
“…Despite study results indicating Asians to be at higher risk, there is a lack of comprehensive prevalence datasets and extensive research in the Asia-Pacific region [10]. A previous study conducted in Korea reported that 9.1% of patients undergoing medical examinations to have bronchiectasis [14]. Similar to reports from the U.S. and European countries, bronchiectasis in Korea has also indicated its relations to age, gender, a history of tuberculosis, and accompanying respiratory diseases [10,15].…”
Section: Introductionmentioning
confidence: 96%